2018
DOI: 10.1371/journal.pone.0204592
|View full text |Cite
|
Sign up to set email alerts
|

Dog ownership satisfaction determinants in the owner-dog relationship and the dog's behaviour

Abstract: Dog ownership satisfaction relates to the quality of life of both owner and dog, and when seriously compromised may even lead to dog abandonment. Knowledge on determinants of dog ownership satisfaction is limited, obstructing solutions for promoting satisfaction, and here we quantified causes making dog owners less than very satisfied with their dog. We focused on the owner perceived relationship with the dog, unwanted dog behaviour, and dog obedience class attendance. The study population included only few se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 48 publications
2
41
0
1
Order By: Relevance
“…For the translation step, a Dutch native speaker, who was also fluent in English at an academic level and who had worked with the original MDORS, translated the original English questionnaire to Dutch (version T1). They additionally compared their translation to a separate MDORS translation, which had been used in a previous study (version T2) [29]. A Dutch language expert subsequently checked the translations for grammar and spelling mistakes, or strange formulations.…”
Section: Methodsmentioning
confidence: 99%
“…For the translation step, a Dutch native speaker, who was also fluent in English at an academic level and who had worked with the original MDORS, translated the original English questionnaire to Dutch (version T1). They additionally compared their translation to a separate MDORS translation, which had been used in a previous study (version T2) [29]. A Dutch language expert subsequently checked the translations for grammar and spelling mistakes, or strange formulations.…”
Section: Methodsmentioning
confidence: 99%
“…In preliminary work by the authors, we found an association between impact on owner lifestyle, as measured with MDORS, and problem behaviour, using C-BARQ; dog directed aggression, separation problems, and training issues (miscellaneous problems) were all associated with a negative impact on owner lifestyle (perceived costs). This work has been followed up by Herwijnen et al who found similar relationships between aggression and disobedience, and perceived costs and satisfaction with ownership [57]. However, those authors did not examine the relationship between MDORS and a wide range of other behaviour problems.…”
Section: The Family's Quality Of Lifementioning
confidence: 98%
“…It was diagnosed in 16-72% (depending on the aggression type) of 1,644 dogs included in a retrospective case series evaluation of medical records [18] and reported by as many as 36% of 174 South Korean dog owners [9]. Also, aggression was the main reason for behavioural consultation in a study population of 140 dogs, of which 129 were desexed [23], and aggression associated with high perceived costs of dog ownership and with reduced ownership satisfaction [24]. Strongly reduced ownership satisfaction due to a dog's unwanted behaviour may ultimately lead to dog relinquishment [25,26,27] or euthanasia [28].…”
Section: Introductionmentioning
confidence: 99%